PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE QUANTUM LEARNING (QL) DALAM PEMBELAJARAN IPS DI KELAS V SD - Dola, Rahma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research was done based on research her observation about learning IPS with teacher central method, in short, the students are not involved and active in teaching learning process. The purpose of this research is to describe improvement of the result in IPS teaching learning process by using Quantum Learning (QL) toward the fifth grade of students in SDN 17 Koto hilalang Balingka. The kind of this research is PTK with qualitative and quantitative approach. Cycles of the total result I 64% improve toward II cycles become 97%. Hence, QL method can improve the result of students learning process in learning IPS in the Fifth grade of SDN 17 Koto Hilalang Balingka .   Kata Kunci : hasil belajar, IPS , dan metode quantum learning (ql)